Parental physical activity is associated with objectively measured physical activity in young children in a sex-specific manner: the GECKO Drenthe cohort - Silvia I. Brouwer; Leanne K. Küpers; Lotte Kors; Anna Sijtsma; Pieter J. J. Sauer; Carry M. Renders; Eva Corpeleijn (BMC, 2018)
Abstract Background Physical activity (PA) is important in combating childhood obesity. Parents, and thus parental PA, could influence PA in young children. We examined whether the time spent at different intensities of PA and the type of parental PA are associated with the PA of children aged 4-7 years, and whether the associations between child-parent pairs were sex-specific. Methods All the participants were recruited from the Groningen Expert Center for Kids with Obesity (GECKO) birth cohort (babies born between 1 April 2006 and 1 April 2007 in Drenthe province, the Netherlands) and were aged 4-7 years during measurement. PA in children was measured using the ActiGraph GT3X (worn at least 3 days, ≥10 h per day). PA in parents was assessed using the validated SQUASH questionnaire. Results Of the N = 1146 children with valid ActiGraph data and 838 mothers and 814 fathers with valid questionnaire data, 623 child-parent pairs with complete data were analysed. More leisure time PA in mothers was associated with more time spent in moderate-to-vigorous PA (MVPA) in children (Spearman r = 0.079, P < .05). Maternal PA was significantly related to PA in girls, but not boys. More time spent in maternal vigorous PA, in sports activity, and leisure time PA, were all related to higher MVPA in girls (Spearman r = 0.159, r = 0.133 and r = 0.127 respectively, Pall < .05). In fathers, PA levels were predominantly related to PA in sons. High MVPA in fathers was also related to high MVPA in sons (r = 0.132, P < 0.5). Spending more time in light PA was related to more sedentary time and less time in MVPA in sons. Conclusions Higher PA in mothers, for instance in leisure activities, is related to higher PA in daughters, and more active fathers are related to more active sons. To support PA in young children, interventions could focus on the PA of the parent of the same sex as the child. Special attention may be needed for families where the parents have sedentary jobs, as children from these families seem to adopt more sedentary behaviour.